Fashioning clothing with and for mature women: a small-scale sustainable design business model. Issue 1 (14th January 2019) - Townsend, Katherine; Kent, Anthony; Sadkowska, Ania
Abstract : Purpose: An ageing population in the developed world has become a significant topic in the contemporary research agenda. The purpose of this paper is to report on the development of a new small-scale business model based on facilitating in-depth understanding and responding to mature female consumers' needs and expectations towards fashionable clothing. Design/methodology/approach: Two complementary approaches are used: interpretative phenomenological analysis allows the researchers to employ the life-course perspective and to develop in-depth understanding of individuals' present experiences in relation to their past. Action research offers the possibility to develop participatory, co-design processes based on collective creativity and mutual knowledge exchange between the stakeholders. Findings: The research finds a strong interest in fashionable clothing by women, irrespective of their age. The action-based co-design process involving collaborative encounters with mature consumers creates a dynamic capability for alternative fashion design methodologies. This approach can contribute to a small-scale fashion business model for the mature women's fashion market. Practical implications: The women in the study stress the need for a more inclusive design process and expressed a willingness to buy from a brand/retailer who would offer them such a collaborative opportunity. There are practical implications for how a more flexible sizing approach to the design of fashion for older women could be implemented. Originality/value: This research makes a contribution to practice-based design solutions for mature women and a new inclusive business model based on emotional durability. The innovative methodological approach contributes to the field of ethical and sustainable fashion design.